Recontextualizing Schooling Within an Inuit Community - Douglas, Anne (Canadian Journal of Education/Revue canadienne de l’éducation, 1994)
Inuit community members in Baffin Island are learning to manage formal schooling, and at the same time modifying that institution so that it reflects their own community context. Yet finding the right fit between schooling and a new cultural context presents a challenge. Many Inuit find problematical the new values schooling introduces into the community. This article proceeds from the assumption that the practices and values of formal schooling historically have been superimposed upon already existing indigenous institutions, which, in many cases, remain invisible to “southern” educators. The concept “formal schooling” as used here is not restricted to classroom values and practices, but denotes the whole schooling system and extends to include the system’s many roles and varied content. Les membres de la communauté inuite de l’île de Baffin apprennent à gérer les pro- grammes scolaires officiels tout en leur apportant des modifications relevant du contexte communautaire. La recherche du juste équilibre entre les programmes d’études officiels et un nouveau contexte culturel constitue toutefois un défi. L’école introduit de nouvelles valeurs que de nombreux membres de la communauté estiment problématiques. L’auteure pose comme hypothèse que les pratiques et les valeurs de l’école officielle sont depuis toujours surimposées à des institutions autochtones déjà existantes qui, dans de nombreux cas, demeurent invisibles aux éducateurs “du Sud.” Ici, le concept d’“école officielle” ne se limite pas aux valeurs et pratiques rattachées à la classe, mais englobe l’ensemble du système scolaire, notamment les nombreux rôles et les contenus divers de ce système.